Genome‐wide genotyping of a novel Mexican Chile Pepper collection illuminates the history of landrace differentiation after Capsicum annuum L. domestication. (11th July 2018) - Taitano, Nathan; Bernau, Vivian; Jardón‐Barbolla, Lev; Leckie, Brian; Mazourek, Michael; Mercer, Kristin; McHale, Leah; Michel, Andrew; Baumler, David; Kantar, Michael; van der Knaap, Esther
Abstract: Studies of genetic diversity among phenotypically distinct crop landraces improve our understanding of fruit evolution and genome structure under domestication. Chile peppers ( Capsicum spp. L.) are economically valuable and culturally important species, and extensive phenotypic variation among landraces exists in southern Mexico, a center of C. annuum diversity. We collected 103 chile pepper seed accessions from 22 named landraces across 27 locations in southern Mexico. We genotyped these accessions with genotyping by sequencing (GBS), yielding 32, 623 filtered single‐nucleotide polymorphisms. Afterward, we genotyped 32 additional C. annuum accessions from a global collection for comparison to the Mexican collection. Within the Mexican collection, genetic assignment analyses showed clear genetic differentiation between landraces and clarified the unique nature of the Tusta landrace. Further clustering analyses indicated that the largest fresh‐use Chile de Agua and dry‐use Costeño landraces were part of separate clades, indicating that these two landraces likely represent distinct populations. The global accessions showed considerable admixture and limited clustering, which may be due to the collapse of use‐type divisions outside of Central America. The separation of the Mexican landraces in part by fruit morphology related to use highlights the relevance of this use‐type morphological diversity for plant breeders and the utility of fruit development variation for evolutionary biologists.